Disadvantaged by chance? Examining the persistence of relative age effects on educational achievement - Benz, Robin; Ackermann, Tobias (Frontiers in Education, 2025)
Most education systems have arbitrarily chosen annual cut-off dates for school enrolment, which create age differences of up to a year within a cohort of pupils. Prior research has shown that the oldest in a cohort systematically outperform their relatively younger peers. Yet, little is known about the temporal persistence of relative age effects in education. In this article, we investigate how relative age effects on educational achievement evolve over different stages of compulsory education. Drawing on administratively linked test score data comprising entire student cohorts in Northwestern Switzerland, we employ two complementary analytical approaches to examine for how long the advantages of relatively older pupils prevail. The results indicate that relative age effects diminish the more pupils progress in their educational careers. However, effects of relative age at school enrolment are still identifiable beyond sixth grade, which marks the transition into secondary education in Switzerland.